2004
DOI: 10.1007/s11178-005-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some naphthyl-substituted nitrogen heterocycles on the basis of (Z)-3-chloro-3-(2-naphthyl)propenal

Abstract: β-Naphthyl-substituted derivatives of pyrazole, benzodiazepine, isoxazole, and pyrimidine were synthesized by reactions of (Z)-3-chloro-3-(2-naphthyl)propenal with hydrazine, o-phenylenediamine, hydroxylamine, and formamide, respectively.(Z)-3-Chloro-3-(2-naphthyl)propenal (I), which is readily available from 2-acetylnaphthalene via Vilsmeier-Haack reaction [1], is a reactive synthon for the preparation of various organic compounds containing a naphthalene fragment. The chlorine atom at the C=C bond in molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The IR and 1 H NMR spectra of compound IV essentially differ from the spectra of 5-(2-naphthyl)-pyrazole (V) we have synthesized previously [2]. In the 1 H NMR spectrum of compound IV alongside the multiplet belonging to the protons of the naphthyl fragment two doublets were identified located at d 6.85 and 7.77 ppm with a coupling constant J 2.2 Hz corresponding to the =CH groups of the pyrazole ring, whereas in the spectrum of 5-(2-naphthyl)pyrazole (V) the protons of the heterocycle appeared as doublets at d 7.0 and 7.95 ppm, 3 J 6 Hz [2]. The relatively small value of the coupling constant observed for compound IV suggests by analogy with the published data on the spectra of related substances [4,5] that it is 4 J , and thus VASHKEVICH et al…”
Section: Z-3-(2-naphthyl)-3-chloro-2-propen-1-al (I) Easilymentioning
confidence: 71%
See 3 more Smart Citations
“…The IR and 1 H NMR spectra of compound IV essentially differ from the spectra of 5-(2-naphthyl)-pyrazole (V) we have synthesized previously [2]. In the 1 H NMR spectrum of compound IV alongside the multiplet belonging to the protons of the naphthyl fragment two doublets were identified located at d 6.85 and 7.77 ppm with a coupling constant J 2.2 Hz corresponding to the =CH groups of the pyrazole ring, whereas in the spectrum of 5-(2-naphthyl)pyrazole (V) the protons of the heterocycle appeared as doublets at d 7.0 and 7.95 ppm, 3 J 6 Hz [2]. The relatively small value of the coupling constant observed for compound IV suggests by analogy with the published data on the spectra of related substances [4,5] that it is 4 J , and thus VASHKEVICH et al…”
Section: Z-3-(2-naphthyl)-3-chloro-2-propen-1-al (I) Easilymentioning
confidence: 71%
“…prepared from 2-acetonaphthone by VilsmeierHaack reaction [1] contains two reactive sites (C=O and =CCl) that permits an effective application of the compound to building up versatile heterocyclic systems including a naphthalene fragment: benzodiazepine, isoxazole, pyrimidine [2], and quinoline [3]. We formerly demonstrated that the reaction between chloropropenal I and hydrazine hydrate was a convenient procedure for preparation of 5-(2-naphthyl)pyrazole [2].…”
Section: Z-3-(2-naphthyl)-3-chloro-2-propen-1-al (I) Easilymentioning
confidence: 99%
See 2 more Smart Citations
“…Another essential limitation of this reaction (Scheme ) was the structure of the starting 2‐alkenal. It was established that 3‐chloro‐propenal 32 and 2‐substituted amino‐propenal 34 reacted with aromatic and aliphatic 1,2‐diamines to deliver diazepine derivatives 33 and 35 , respectively (Scheme ); this reactivity could be explained by the participation of alternative reaction sites in the process. For comparison, it should be noted that such a result is characteristic of the reaction between 2‐enones and 1,2‐diamines, as supported by numerous experiments…”
Section: Imidazoles Imidazolines Imidazolidines and Their Derivatmentioning
confidence: 99%